The monastery complex in Tzintzuntzan. Province, doctrine and architecture for evangelization (Tzintzun, Revista de Estudios Históricos, 2021)
Between 1526 and 1565, the monastery complex in Tzintzuntzan was the most important religious see of the Franciscan Friars of the Custody of San Pedro and San Pablo in Michoacán and Jalisco, since it was from there that the evangelization and indoctrination of the Indians of the West of New Spain was organized. Very important religious men lived in the convent during this period, such as Brother Martín de la Coruña, Brother Maturino Gilberti, Brother Jacobo Daciano, Brother Juan Focher, Brother Pedro de Pila and Brother Diego Muñoz. After ceding command of the province to the Valladolid convent, as the viceregal authorities and the order took on more foundations north of the Lerma river, the complex lost its hierarchy and entered an economic crisis period. Nevertheless, it continued to be the heart of Tzintzuntzan, where numerous social and cultural practicestook place, up to just before the secularization of the doctrine in 1766. Similarly, the friars played a fundamental role in the life of the towns under their care, since they actively participated in all important decisions.
Keywords: franciscans; doctrine; San Pedro and San Pablo province; indian hospital; uses of space